Environmental, Social, and Governance Disclosure as Pathway to Business Sustainability on the Mining Companies in Indonesia and America - Putriningtyas, Indira; Widiastuti, Ni Putu Eka; Sjam, Juska Meidy Enyke (Jurnal Aplikasi Manajemen, 2024)
This research aims to examine the influence of Environmental, Social, and Governance Disclosure, Capital Structure, and Managerial Ownership on Financial Performance, with Good Corporate Governance as a moderating variable. The research focuses on Indonesian and American mining companies listed on the Indonesian Stock Exchange and the New York Stock Exchange. The number of samples in this research was 250 mining companies in Indonesia and 75 mining companies in America. The research employs purposive sampling method to select the sample. The results show that Environmental, Social, and Governance Disclosure negatively affects financial performance in both Indonesia and America, indicating that higher levels of Environmental, Social, and Governance Disclosure are associated with lower financial performance. Capital structure, as measured in Debt to Asset Ratio, has a negative influence on Financial Performance both in Indonesia and America, implying that greater reliance on debt is linked to poorer financial performance. Managerial Ownership exhibits a positive influence on financial performance in both Indonesia and America, suggesting that higher levels of managerial ownership are associated with better financial performance. In Indonesia, Good Corporate Governance as a moderation strengthens the influence of Environmental, Social, and Governance Disclosure on financial performance. However, in America, Good Corporate Governance does not have a similar strengthening influence. Good Corporate Governance as a moderation also strengthens the influence of Capital Structure on financial performance in Indonesia, but not in America. Good Corporate Governance as a moderation does not enhance the influence of Managerial Ownership on financial performance in both Indonesia and America.